2021
DOI: 10.1186/s40337-021-00419-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on adolescents with eating disorders: a cohort study

Abstract: Background There is a noticeable lack of evidence regarding the impact of COVID-19 and the associated lockdown on young people with eating disorders. The goals of this study were 1) to examine characteristics of adolescents presenting for eating disorder (ED) assessment since the onset of the COVID-19 pandemic; 2) to compare adolescents presenting for ED assessment since the onset of the COVID-19 pandemic to those that presented for assessment 1 year previously; 3) to examine implications of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 18 publications
6
73
1
Order By: Relevance
“…The second theme identified was an investigation of the perceived impact of the pandemic on eating disorder or mental health symptoms. Twenty‐two studies examined this theme, with 16 studies sampling clinical populations (participant n s = 12–1,021; Akgül et al, 2021 ; Baenas et al, 2020 ; Branley‐Bell & Talbot, 2020 ; Favreau et al, 2021 ; Graell et al, 2020 ; Machado et al, 2020 ; Quittkat et al, 2020 ; Richardson et al, 2020 ; Schlegl, Maier, Meule, & Voderholzer, 2020 ; Schlegl, Meule, Favreau, & Voderholzer, 2020 ; Shaw et al, 2021 ; Spettigue et al, 2021 ; Spigel et al, 2021 ; Termorshuizen et al, 2020 ; Vitagliano et al, 2021 ; Vuillier et al, 2021 ) and six studies sampling non‐clinical populations (participant n s = 90–5,469; Athanasiadis et al, 2021 ; Buckley et al, 2021 ; Coimbra et al, 2021 ; Keel et al, 2020 ; Phillipou et al, 2020 ; Robertson et al, 2021 ). In all cases, the authors developed their own items assessing perceived impacts of COVID‐19.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second theme identified was an investigation of the perceived impact of the pandemic on eating disorder or mental health symptoms. Twenty‐two studies examined this theme, with 16 studies sampling clinical populations (participant n s = 12–1,021; Akgül et al, 2021 ; Baenas et al, 2020 ; Branley‐Bell & Talbot, 2020 ; Favreau et al, 2021 ; Graell et al, 2020 ; Machado et al, 2020 ; Quittkat et al, 2020 ; Richardson et al, 2020 ; Schlegl, Maier, Meule, & Voderholzer, 2020 ; Schlegl, Meule, Favreau, & Voderholzer, 2020 ; Shaw et al, 2021 ; Spettigue et al, 2021 ; Spigel et al, 2021 ; Termorshuizen et al, 2020 ; Vitagliano et al, 2021 ; Vuillier et al, 2021 ) and six studies sampling non‐clinical populations (participant n s = 90–5,469; Athanasiadis et al, 2021 ; Buckley et al, 2021 ; Coimbra et al, 2021 ; Keel et al, 2020 ; Phillipou et al, 2020 ; Robertson et al, 2021 ). In all cases, the authors developed their own items assessing perceived impacts of COVID‐19.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (participant n s = 48–8,613) assessed a cohort of participants during the pandemic and compared their symptom severity to a different cohort assessed prior to the pandemic (Calugi et al, 2021 ; Christensen et al, 2021 ; Kim et al, 2021 ; Koenig et al, 2021 ; Muzi et al, 2021 ; Richardson et al, 2020 ; Spettigue et al, 2021 ; Zhou & Wade, 2021 ). Only three of these studies (37%) reported no significant differences in certain demographic or clinical characteristics between the two cohorts (Calugi et al, 2021 ; Keonig et al 2021; Zhou & Wade, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 10 , 11 A recent single-center study at an adolescent eating disorder program found that, across all eating disorders, 40% of newly diagnosed patients cited the pandemic as a trigger for their eating disorder. 21 Interviews conducted with adults with an eating disorder revealed an exacerbation of symptoms that was associated with increased anxiety, social isolation, and reduced contact with their treatment teams. 9 , 22 Moreover, adults also reported worsening eating disorder symptoms in conjunction with a lack of distractions and constant exposure to stressful messages on social media.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the significant impact of the pandemic on the increase in eating disorders in adolescents was measured by comparing the number of urgent hospitalizations during the same period with the previous year, which increased by 63% [ 24 ]. The increase in visits and hospitalization compared to the year before COVID-19 was detected in a study involving children and adolescents with eating disorders in order to evaluate the effectiveness of treatments combined with telepsychotherapy for outpatients of a day-hospital.…”
Section: Introductionmentioning
confidence: 99%